2022
DOI: 10.3390/polym14040787
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Biopolymer and Fiber Inclusions on Unconfined Compressive Strength of Soft Soil

Abstract: The utilizing of traditional chemical stabilizers could improve soil engineering properties but also results in brittle behavior and causes environmental problems. This study investigates the feasibility of the combined utilization of an ecofriendly biopolymer and fiber inclusions as an alternative to traditional cement for reinforcing soft soil. A series of unconfined compression tests were conducted to examine the combined effect of the biopolymer and fibers on the stress–strain characteristics, strength imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…At the same time, the spatial network structure formed by the fibers provides a space skeleton for the biopolymer reinforced soil. When the soil is subjected to external force, the existence of the space skeleton increases the ductility and reduces the brittleness of the soil [28]. Under the coaction of biopolymer and fibers, it shows multiplying effect The schematic diagram of the interaction among biopolymer, fibers and soil particles is shown in figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the spatial network structure formed by the fibers provides a space skeleton for the biopolymer reinforced soil. When the soil is subjected to external force, the existence of the space skeleton increases the ductility and reduces the brittleness of the soil [28]. Under the coaction of biopolymer and fibers, it shows multiplying effect The schematic diagram of the interaction among biopolymer, fibers and soil particles is shown in figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…Microorganism-based biopolymers, including xanthan gum, gellan gum, and dextran, are polysaccharides produced by Xanthomonas campestris, forming helical structures mainly composed of two glucose, two mannoses, and one glucuronic acid unit [12]. Previous studies, such as those by Chen et al [13]. Overall, the inter-particle relations and strengthening behavior of the biopolymer-soil matrices are considered suitable for subgrade treatment owing to their net-zero benefits and mechanical strength improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been widely recognized that the improvement of soil mass by adding a variety of composite materials with a certain mixing ratio is better than that by adding a single material [ 30 , 31 ]. At present, the addition of lime-ash or cement-lime mixes to soil is the most-used method for the improvement of loess subgrade, while few studies were found on the improved materials improve loess subgrade by combining new materials with traditional materials [ 32 ].…”
Section: Introductionmentioning
confidence: 99%